A bulky and flexible electrocatalyst for efficient hydrogen evolution based on the growth of MoS2 nanoparticles on carbon nanofiber foam1. Issue 9 (7th March 2015) - Guo, Xin; Cao, Guo-lin; Ding, Fei; Li, Xinyuan; Zhen, Shuyu; Xue, Yi-fei; Yan, Yi-ming; Liu, Ting; Sun, Ke-ning
<x xml:space="preserve">Abstract</x> A bulky and flexible MoS2/CNF foam was prepared and used as a high performance HER electrocatalyst.